Chylothorax caused by blunt trauma: Case review and management proposal. (August 2020) - Bacon, Brandon T.; Mashas, Wayne
Abstract: Chylothorax is a potentially devastating complication of lymphatic trauma of the thorax. To date, no recommendations have provided decision making support for prompt definitive treatment. We present a 53 year old male involved in a motor vehicle collision sustaining 9 left rib fractures with flail segments. He was treated non-operatively with a chest tube and no fat diet. A Case report review was performed and a proposed guideline for managing blunt trauma chylothorax in adult patients was developed. In low-output chylothorax, effective initial treatment begins with a no fat diet and chest tube. We propose that a low output leak be defined as <500 mL of initial output or <500 mL/day and can be managed non-operatively in nearly 100% of patients. High output injuries of >1000 mL of initial output will require surgical intervention and should be considered for prompt definitive care.